Rola nauczyciela edukacji wczesnoszkolnej w kształtowaniu (się) przyrodniczej wiedzy naukowej dziecka - Banaszak, Marek (Studia Edukacyjne, 2020)
The text is about the competences of an early education teacher in developing the student’s natural science knowledge. Selected typologies of the teacher’s competences and a constructivist approach towards the student’s knowledge are presented. Moreover, the text shows that experience is a particularly effective method of improving the child’s skills and knowledge related to nature at an early education level.